The fabrication of RC engine model crankshaft / Mohd. Shairizal Mohd. Shaite and Khairulnizam Md. Said - Mohd. Shaite, Mohd. Shairizal; Md. Said, Khairulnizam (2001)
The title of our project is the fabrication of the "RC engine model crankshaft". In this project we need to fabricate a model crankshaft for the remote-control engine. The material we use for the fabrication process is the mild steel, as it possesses the characteristics that we need for the machining work. This project begins with the drawings, then continues with the machining process and finally to the preparation of the report. But the concentration will be given on the machining process, as it is the most important part for this fabrication process. For an easy understanding, the machining process is divided into seven stages and in each stage, a detailed explanation of the process was given. Besides the pictures given in every stage, several pieces of photographs are also provided to give a clear view of the machining works. In this project, the application of the machines such as the lathe and drilling machine is a must as a mean to achieve our mission. Besides that, other equipment which are also important are the vernier caliper and the ruler. They are used for the measurement purpose. Due to several problems, we have to do the machining process for three times in order to get the best product in terms of its quality and the precision of measurements.